Effect of Wild-type p53 Gene Transfection on the Growth and Radiotherapeutic Sensitivity of Human Glioma Cells - 项炜 朱贤立 赵洪洋 (Journal of Huazhong University of Science and Technology. Medical sciences, 2005)
Summary： To evaluate the effect of wild type p53 gene on the growth and radiotherapeutic sensitivity of human glioma cells, plasmid PC53 SN3 carrying wild type p53 gene was transfected into U251 cells, p53 gene expression in transfected cells was detected by RT PCR, and the cell growth inhibition and apoptosis in the absence or presence of irradiation were assessed by MTT and flow cytometry. The transfection of p53 gene into U251 cells was confirmed by RT PCR. MTT showed that p53 gene alone induced strong inhibitory effect on the growth of U251 cells （inhibition rate （IR）： （79.60±5.69）%）, The killing effect of irradiation alone on U251 cells was not strong （IR： （17. 06±4.35）%, （17.39±1.67）%, （18.73±4.68）%） and increased with the irradiation doses （3, 6, 9 Gy）. When combined treatment of wild-type p53 gene transfection and irradiation was used, the effect was significantly increased （IR：（80.60±5.35）%, （90.30＋1.67） %, （91.30±2.01） %）. Theapoptosis rate of U251 cells induced by p53 gene transfectionwas 17.38 %. The rate induced by irradiation increased （4. 61%, 4. 84%, 5. 40 %） with the irradiation doses （3, 6, 9 Gy）. Theapoptosis rate was also significantly increased （17.80%, 20.03%, 22.34%） after combined treatment of p53 and irradiation with different doses （3, 6, 9 Gy）. It is concluded that wildtype p53 gene and irradiation could result in synergistic inhibitory effect on the growth of human glioma cells.